The complete chloroplast genome sequence of an endangered species, Oncodostigma hainanense. Issue 1 (2nd January 2019) - Chen, Yukai; Zhang, Jinwen; Zhang, Ying; Li, Dong-Lin; Yang, Yong
Abstract: Oncodostigma hainanense is an endangered species with extremely small populations due to human activities in China. This study presents the chloroplast genome of the plant by de novo assembly using the whole-genome sequencing data. The size of the complete chloroplast genome was 160, 497 bp in length, comprising a large single copy region (LSC) of 89, 424 bp, a small single copy region (SSC) 18, 948 bp, and inverted repeat regions (IRS) of 26, 061 bp. A total of 135 genes, including 85 protein-coding genes, 42 tRNA genes and eight rRNA genes, were predicted from the chloroplast genomes. Among them, 17 genes occur in IRS, containing six protein-coding genes, seven tRNA genes and four rRNA genes. The GC content of O. hainanense was 35.59%. Phylogenetic analysis with seven other species revealed that O. hainanense was clustered with Annona cherimola .